A single dose of recombinant adenoviral vector rabies vaccine expressing two copies of glycoprotein protects mice from lethal virus challenge - Li, Qunlong; He, Hongzhuan; Zhou, Yuxi; Wang, Jihong; Chen, Huan; Liu, Hui (The Journal of Infection in Developing Countries, 2024)
Introduction: Rabies is a fatal infectious disease, that poses a major public health threat in developing countries. With an annual death toll of approximately 59,000, more than half of which are children, an urgent need exists for a safe, affordable, and effective preventive measure against rabies virus infection. Methodology: A recombinant rabies vaccine called Ad5-dRVG was constructed by introducing two copies of the rabies virus glycoprotein into a human adenoviral vector. Virus-neutralizing assays and virus challenge experiments were employed to evaluate the Ad5-dRVG vaccine. Results: Our findings demonstrate that a single dose of Ad5-dRVG, administered either intramuscularly or orally, elicited significantly stronger immune responses than Ad5-RVG. Moreover, both vaccines provided complete protection in mice. Notably, the vaccine exhibited remarkable efficacy even at low doses, suggesting potential cost reduction in production. Conclusions: The development of the Ad5-dRVG recombinant rabies vaccine represents a significant advancement in rabies prevention. Its enhanced immunogenicity, demonstrated efficacy and potential cost savings make it a promising candidate for widespread use.